Total cholesterol, alanine aminotransferase and the risk of primary liver cancer: A population-based prospective study - Sun, Miaomiao; Wang, Wanchao; Liu, Xining; Wang, Yiming; Cui, Haozhe; Liu, Siqing; Cao, Liying (Medicine (Baltimore), 2021)
Previous studies have shown that serum total cholesterol (TC) and serum alanine aminotransferase (ALT) are associated with liver cancer risk. However, the common contribution of TC and normal-high ALT to primary liver cancer (PLC) has not been reported. We aim to assess the separate and joint effect of low TC level and normal-high ALT level on the risk of PLC, a large prospective cohort was conducted in our study.The participants were divided into 4 groups via the cross-matching method according to TC [low level (-)/non-low level (+)] and ALT [normal level (-)/normal-high level(+)] status, and using the lower quartile value of TC and the upper quartile value of ALT as a threshold, respectively. Incident PLC was confirmed by review of medical records. Cox proportional hazards regression models and interactive additive models were used to evaluate whether the joint effect of low TC level and normal-high ALT level is associated with the risk of PLC.During 1,248,895 person-years follow-up, 298 participants were diagnosed with PLC among 114,972 subjects. In male population, TC < 4.24 mmol/L was group "TC (-)"; TC ≥ 4.24 mmol/L was group "TC (+)"; ALT < 23 U/L was group "ALT (-)": 33 U/L ≥ ALT ≥ 23 U/L was group "ALT (+)". Compared with the group "TC (+)", group "ALT (-)", respectively, the adjusted hazard ratio (HR) and 95% confidence interval (95%CI) for PLC risk was 1.74 (1.36-2.25) in group "TC (-)" and 1.49 (1.15-1.94) in group "ALT (+)". In combinatorial analysis, compared with group "TC (+) and ALT (-)", the significant increased risk of PLC were observed in group "TC (+) and ALT (+)" (HR = 1.41; 95% confidence intervals [CI]: 1.02-1.95), group "TC (-) and ALT (-)" (HR = 1.67; 95%CI: 1.24-2.27) and group "TC (-) and ALT (+)" (HR = 2.72; 95%CI: 1.81-4.09), respectively. However, no statistical significance was found among female.The separate and joint effect of low TC level and normal-high ALT level was observed for PLC risk in males. When combined, individuals with coexistence of low TC level and normal-high ALT level significantly increase the risk of PLC.